Virtual Reality for Rich Interaction with Cultural Heritage Sites - AlMuraikhi, Nouf; AlMalki, Fatima; AlDahnim, Fadeela; Halabi, Osama (HCI in Games: Serious and Immersive Games, 2021)
Archaeological sites represent an important dimension of history and civilization. The aim of this work is to is to document the heritage buildings as part of a preservation process of the heritage environment by creating a three-dimensional model of one heritage site in Qatar including all the details of the site using photogrammetry technique. Different techniques for constructing the 3D model of the site has been explored and tested. The model then rendered in a game engine to create interactive virtual reality (VR) experience. Artifacts integrated with the VR environment, moreover, smart avatars that represent people’s life and appearance during that period were created in order to bring the place back to life again. Usability, game experience, and simulator sickness evaluation were carried out to test the system.